Ankle-Brachial Index determination and peripheral arterial disease diagnosis by an oscillometric blood pressure device in primary care: validation and diagnostic accuracy study. Issue 5 (25th October 2012) - Nelson, Mark R; Quinn, Stephen; Winzenberg, Tania M; Howes, Faline; Shiel, Louise; Reid, Christopher M
Abstract : Objectives: To determine the level of agreement between a 'conventional' Ankle-Brachial Index (ABI) measurement (using Doppler and mercury sphygmomanometer taken by a research nurse) and a 'pragmatic' ABI measure (using an oscillometric device taken by a practice nurse) in primary care. To ascertain the utility of a pragmatic ABI measure for the diagnosis of peripheral arterial disease (PAD) in primary care. Design: Cross-sectional validation and diagnostic accuracy study. Descriptive analyses were used to investigate the agreement between the two procedures using the Bland and Altman method to determine whether the correlation between ABI readings varied systematically. Diagnostic accuracy was assessed via sensitivity, specificity, accuracy, likelihood ratios, positive and negative predictive values, with ABI readings dichotomised and Receiver Operating Curve analysis using both univariable and multivariable logistic regression. Setting: Primary care in metropolitan and rural Victoria, Australia between October 2009 and November 2010. Participants: 250 persons with cardiovascular disease (CVD) or at high risk (three or more risk factors) of CVD. Results: Despite a strong association between the two method's measurements of ABI there was poor agreement with 95% of readings within ±0.4 of the 0.9 ABI cut point. The multivariable C statistic of diagnosis of PAD was 0.89. Other diagnostic measures were sensitivity 62%, specificity 92%, positive predictive value 67%, negative predictive value 90%, accuracy 85%, positive likelihood ratio 7.3 and the negative likelihood ratio 0.42. Conclusions: Oscillometric ABI measures by primary care nurses on a population with a 22% prevalence of PAD lacked sufficient agreement with conventional measures to be recommended for routine diagnosis of PAD. This pragmatic method may however be used as a screening tool high-risk and overt CVD patients in primary care as it can reliably exclude the condition.